Development and Characterization of Hybrids from Native Wine Yeasts - Contreras-Opazo, A; Martinez-Fernandez, C; Ganga-Munoz, M; Garcia-Mena, V (2012)
For commercial purposes, the winemaking industry is constantly searching for new yeast strains. Historically, this has been achieved by collecting wild strains and selecting the best for industrial use through an enological evaluation. Furthermore, the increasing consumer demands have forced the industry to incorporate new strategies such as genetic engineering to obtain improved strains. In response to the lack of public acceptance of this methodology, alternative strategies based on breeding have gained acceptance in recent years. Through the use of conjugation of individual spores without the support of genetic engineering methods we generated intraspecific hybrids from wild strains with outstanding enological characteristics and interdelta fingerprinting was used to confirm the hybrid condition. A detailed enological characterization of the hybrids in synthetic and natural must indicates that physiological parameters such as sporulation, residual sugar, ethanol yield and total nitrogen uptake are within the levels determined for the parental strains, however, other parameters such as growth rate, lag phase and ethanol production show statistical differences with some parental or commercial strains. These findings allow us to propose these hybrids as new wine-making strains.